How Well Do We Understand Soft Power? - Akarapisit, Arisara (Siam University Journal of Business Administration, 2025)
Soft Power is not just the promotion of a culture but it also plays a role encompassing various dimensions working together as a mechanism. The soft power concept was coined in the late 1980s and defined as the opposite of the hard power one. A country’s soft power rests primarily on three resources: its culture, its political values and its foreign policy. Three power currencies that generate gentle attraction are benignity, brilliance, and beauty. When the three power currencies have transformed into the soft power, public diplomacy is used as a means of promoting the country’s soft power. According to the Global Soft Power Index, the countries filled the top three spots over the past three years were the USA, the UK, and Germany. The lesson learned from top soft power nations shows that four key success factors are vision and role of the government, national self-esteem, consistency of creating popularity, and the target government and public acceptance.